Comparison of Arachis monticola with Diploid and Cultivated Tetraploid Genomes Reveals Asymmetric Subgenome Evolution and Improvement of Peanut. Issue 4 (28th November 2019) - Yin, Dongmei; Ji, Changmian; Song, Qingxin; Zhang, Wanke; Zhang, Xingguo; Zhao, Kunkun; Chen, Charles Y.; Wang, Chuantang; He, Guohao; Liang, Zhe; Ma, Xingli; Li, Zhongfeng; et al.
Abstract: Like many important crops, peanut is a polyploid that underwent polyploidization, evolution, and domestication. The wild allotetraploid peanut species Arachis monticola ( A. monticola ) is an important and unique link from the wild diploid species to cultivated tetraploid species in the Arachis lineage. However, little is known about A. monticola and its role in the evolution and domestication of this important crop. A fully annotated sequence of ≈2.6 Gb A. monticola genome and comparative genomics of the Arachis species is reported. Genomic reconstruction of 17 wild diploids from AA, BB, EE, KK, and CC groups and 30 tetraploids demonstrates a monophyletic origin of A and B subgenomes in allotetraploid peanuts. The wild and cultivated tetraploids undergo asymmetric subgenome evolution, including homoeologous exchanges, homoeolog expression bias, and structural variation (SV), leading to subgenome functional divergence during peanut domestication. Significantly, SV‐associated homoeologs tend to show expression bias and correlation with pod size increase from diploids to wild and cultivated tetraploids. Moreover, genomic analysis of disease resistance genes shows the unique alleles present in the wild peanut can be introduced into breeding programs to improve some resistance traits in the cultivated peanuts. These genomic resources are valuable for studying polyploid genome evolution, domestication, and improvement of peanut production and resistance. Abstract : The wild allotetraploid peanut species Arachis monticola ( A. monticola ) is an important and unique link from the wild diploid species to cultivated tetraploid species in the Arachis lineage. A fully annotated sequence of the A. monticola genome and comparative genomics of Arachis species are presented, which reveals asymmetric subgenome evolution and genome‐assisted improvement of peanut production and resistance.